Answer:
f(x-7) = x -12
Step-by-step explanation:
horizontal translation 7 units right: f(x-7)
f(x) = x - 5
f(x-7) = x-7 -5 = x -12
<h3>
Answer: -20</h3>
==========================================================
Work Shown:
Let x be the location of E on the number line.
Since C is the midpoint of E and F, this means we can find C's location by adding E and F together and dividing that sum by 2
midpoint = (endpoint1 + endpoint2)/2
C = (E+F)/2
Plug in E = x, C = -8 and F = 4. Then solve for x
C = (E+F)/2
-8 = (x+4)/2
(x+4)/2 = -8
x+4 = 2(-8) .... multiplying both sides by 2
x+4 = -16
x = -16-4 .... subtract 4 from both sides
x = -20
The location of point E on the number line is -20
-------------
As a check, lets add E and F to get E+F = -20+4 = -16
Then cut this in half to get -16/2 = -8, which is the proper location of point C
This confirms our answer.
D because if you multiply y 8 times it will no longer be doubling the area
Answer:
see attached
Step-by-step explanation:
For x < -6, the function has a slope of -1 and an x-intercept of -6.
For x > -6, the function has a slope of 2 and an x-intercept of -6.
The function given here is not defined at x=6, so there is a hole at (-6, 0).